2012
DOI: 10.3758/s13423-011-0190-x
|View full text |Cite
|
Sign up to set email alerts
|

Semantic picture–word interference is a postperceptual effect

Abstract: Naming a picture is slower while ignoring a semantically related versus an unrelated distractor word (semantic picture-word interference, or PWI). To locate the PWI effect in the word production processing stream (during perceptual encoding, response selection, or afterward), we used the psychological refractory period paradigm, in which participants identified a tone and then, at varying SOAs, named a picture while ignoring a semantically related or unrelated word (following Dell 'Acqua, Job, Peressotti, & Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
74
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(97 citation statements)
references
References 31 publications
21
74
2
Order By: Relevance
“…As in Experiment 1, we observed that the stimulus type effects were additive with SOA for the naming responses, similar to what Schnur and Martin (2012) obtained, but different from Dell'Acqua et al's results. The additivity of the effects of stimulus type and SOA suggests that the semantic and Stroop-like interference occurred at the response-selection stage or later, which challenges the proposal of a pre-selection locus by Dell'Acqua et al Moreover, given that the distractor words were This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…As in Experiment 1, we observed that the stimulus type effects were additive with SOA for the naming responses, similar to what Schnur and Martin (2012) obtained, but different from Dell'Acqua et al's results. The additivity of the effects of stimulus type and SOA suggests that the semantic and Stroop-like interference occurred at the response-selection stage or later, which challenges the proposal of a pre-selection locus by Dell'Acqua et al Moreover, given that the distractor words were This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.…”
Section: Discussionsupporting
confidence: 68%
“…Such an effect on Task 1 RTs could indicate that participants' performance in the present experiment differed from performance in the studies of Dell'Acqua et al (2007) and Schnur and Martin (2012). If so, our pattern of additivity would have no bearing on the discussion regarding the locus of interference effects in dual-task performance.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations